Public Private Partnership in State Highways Model Concession Agreement Second Edition: April 2009 - Planning Commission (Planning Commission, 2009)
The network of state and national highways are critical elements of overland connectivity which is essential for development, growth and national integration. The size and quality of the network are key determinants of competitiveness and growth. There is today a broad consensus that a sustained growth rate of about 9% per annum is necessary for India to make progress in eliminating poverty and achieving a quantum jump in the quality of life of its citizens.
Planning Commission Government of India
Planning Commission Government of India